PHYSIOLOGY AND PREVENTION OF AVIAN FLU - Khoshniyazov Saulat Zhalgasbaevna; Karimov Rashid Parahatovich; Murodov Ozoda Kodirbergan kyzy (Journals Park Publishing, 2023)
The article discusses the physiology and prevention of avian influenza, as well as effective methods for diagnosing, preventing and controlling avian influenza.
Keywords: bacterial diseases, avian influenza, prevention, immunity.